(untitled) (Journal of Laboratory Animal Science, 2024)
The effect of different bedding materials on the performance was studied in eighteen adult female broiler rabbits in three kindlings at Small Animal House, Veterinary College Bangalore. Based on bedding material, rabbits were divided into coconut coir group (T1), ragi straw (T2) and wire mesh group without any bedding material (T3). Litter size and litter weight at birth were6.22±0.37 and 246.30±10.74 in T1 group, 5.66±0.37 and 223.70±11.49 in T2 group and 5.77±0.27 and 224.80±8.242 in T3 group respectively. The average litter size and weight at weaning were 5.72±0.28 and 1488±38.73 in T1 group, 4.94±0.26 and 1202±35.45 in T2 group and 4.50±0.27 and 991±39 in T3 group respectively. The highest litter size and weight at weaning were recorded in T1 group which was significantly different (P<0.05) from other two groups. The results indicate that coir can be suitably used as a low-cost bedding material alternative to ragi straw.